Exponential Polynomials and Nonlinear Differential-Difference Equations. (20th February 2020) - Xu, Junfeng; Rong, Jianxun
Abstract : In this paper, we study finite-order entire solutions of nonlinear differential-difference equations and solve a conjecture proposed by Chen, Gao, and Zhang when the solution is an exponential polynomial. We also find that any exponential polynomial solution of a nonlinear difference equation should have special forms.